2010
DOI: 10.1017/s0018246x10000014
|View full text |Cite
|
Sign up to set email alerts
|

Felony Forfeiture and the Profits of Crime in Early Modern England

Abstract: For much of English history, the law punished felons not just with death, but also with the loss of their possessions. This article examines the practice of felony forfeiture in the sixteenth and early seventeenth centuries, focusing on who profited and with what effects. It argues that recognizing the role such profit-takers played challenges common depictions of the nature and meaning of participation in law and governance. The heightened use of judicial revenues as tokens of patronage under Elizabeth and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Houston argues that the royal almoner was not just a ‘glorified tax collector’, but—in handling suicides' estates and deodands with religious atonement and community peace in mind—an important practitioner of ‘good lordship’. Kesselring gives a rather different angle on felony forfeiture, arguing that the Crown ‘milked’ the profits from felons' property, albeit in an unsystematic way, for financial and political ends. This was hardly ‘good lordship’ in Houston's sense, and Kesselring uses records of conflict over forfeiture to argue that state formation, rather than being consensual and aimed at maintaining the ‘common peace’, could be intensely conflicted.…”
Section: University Of Cambridgementioning
confidence: 99%
See 1 more Smart Citation
“…Houston argues that the royal almoner was not just a ‘glorified tax collector’, but—in handling suicides' estates and deodands with religious atonement and community peace in mind—an important practitioner of ‘good lordship’. Kesselring gives a rather different angle on felony forfeiture, arguing that the Crown ‘milked’ the profits from felons' property, albeit in an unsystematic way, for financial and political ends. This was hardly ‘good lordship’ in Houston's sense, and Kesselring uses records of conflict over forfeiture to argue that state formation, rather than being consensual and aimed at maintaining the ‘common peace’, could be intensely conflicted.…”
Section: University Of Cambridgementioning
confidence: 99%
“…Kesselring gives a rather different angle on felony forfeiture, arguing that the Crown ‘milked’ the profits from felons' property, albeit in an unsystematic way, for financial and political ends. This was hardly ‘good lordship’ in Houston's sense, and Kesselring uses records of conflict over forfeiture to argue that state formation, rather than being consensual and aimed at maintaining the ‘common peace’, could be intensely conflicted. Conflict was the bread and butter of Star Chamber, and Loar ( Sixteenth Century Journal ) uses disputed coroners' inquest verdicts in the court to argue that the emergence of a subjective (as opposed to an objective) understanding of conscience was a bottom‐up phenomenon.…”
Section: University Of Cambridgementioning
confidence: 99%
“…In the case of forfeiture, the potential for profit existed for the crown, for grantees of confiscated estates, for lords to whom tenants' lands reverted, for corrupt administrators, and even for discreet neighbours. 9 But financial interest seems insufficient as an overall explanation for the conduct of the crown or others. Above all, profit fails to explain the selective application and circumscribed imposition of the penalty.…”
mentioning
confidence: 99%
“…Realizing the potential value of their forfeited estates normally depended on the routine work of county officers, whose diligence and probity varied. 25 Cash-strapped mid-Tudor governments pinpointed the system's weakness, without being able to reform it. 26 The revenue commission of 1552 found that the previous year's profits from felons' goods amounted nationwide only to £60.…”
mentioning
confidence: 99%
See 1 more Smart Citation